2022
DOI: 10.1002/advs.202200057
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Accumulation of Histone Variant H2A.Z Regulates Transcriptional States and Histone Modifications in Early Mammalian Embryos

Abstract: Early embryos undergo extensive epigenetic reprogramming to achieve gamete‐to‐embryo transition, which involves the loading and removal of histone variant H2A.Z on chromatin. However, how does H2A.Z regulate gene expression and histone modifications during preimplantation development remains unrevealed. Here, by using ultra‐low‐input native chromatin immunoprecipitation and sequencing, the genome‐wide distribution of H2A.Z is delineated in mouse oocytes and early embryos. These landscapes indicate that paterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…The developments of ultra‐low‐input chromatin immunoprecipitation (ChIP; Brind'Amour et al , 2015) and immunocleavage (ChIC; Skene & Henikoff, 2017) sequencing methods have enabled the study of the dynamic reprogramming of different histone modifications and histone variants during mammalian maternal‐to‐zygotic transition (MZT), which revealed diverse reprogramming patterns for H3K4me3 (Dahl et al , 2016; Zhang et al , 2016), H3K27me3 (Liu et al , 2016; Zheng et al , 2016), H3K9me3 (Wang et al , 2018), H3K36me3 (Xu et al , 2019), H2AK119ub1 (Chen et al , 2021; Mei et al , 2021), H3.3 (Ishiuchi et al , 2020) and H2A.Z (Liu et al , 2022). The study of H3K27ac during zebrafish MZT has revealed distinct dynamics between promoters and distal regions (Zhang et al , 2018; Chan et al , 2019; Miao et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The developments of ultra‐low‐input chromatin immunoprecipitation (ChIP; Brind'Amour et al , 2015) and immunocleavage (ChIC; Skene & Henikoff, 2017) sequencing methods have enabled the study of the dynamic reprogramming of different histone modifications and histone variants during mammalian maternal‐to‐zygotic transition (MZT), which revealed diverse reprogramming patterns for H3K4me3 (Dahl et al , 2016; Zhang et al , 2016), H3K27me3 (Liu et al , 2016; Zheng et al , 2016), H3K9me3 (Wang et al , 2018), H3K36me3 (Xu et al , 2019), H2AK119ub1 (Chen et al , 2021; Mei et al , 2021), H3.3 (Ishiuchi et al , 2020) and H2A.Z (Liu et al , 2022). The study of H3K27ac during zebrafish MZT has revealed distinct dynamics between promoters and distal regions (Zhang et al , 2018; Chan et al , 2019; Miao et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic establishments are also crucial events during oogenesis, oocyte meiotic maturation, OET, and zygotic development. [71,72] Aberrant epigenetic dynamic modifications are associated with decreased female fertility in advanced maternal age. [6,[14][15][16]53,73] Consistent with previous studies, [17,18] we reported the translational repression of DNA methylation factors, including Dnmt1, Dnmt3a/b, and Uhrf1, in aged mouse and human oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous deletion of H2A.Z is embryonically lethal, underlining its importance in early embryo development [ 64 ]. H2A.Z plays a pivotal role in establishing an intricate pattern of gene expression necessary for proper early development in mammals [ 64 , 65 ]. H2A.Z is highly abundant and enriched in the pericentric heterochromatin of undifferentiated cells like mESCs, but not in differentiated mouse or human cells.…”
Section: The 19 Histone H2a Variantsmentioning
confidence: 99%